RESTRUKTURISASI BADAN USAHA MILIK NEGARA (BUMN) SEBAGAI SALAH SATU LANGKAH REFORMASI UNTUK MENGEMBANGKAN PERUSAHAAN: STUDI PADA PT. PERKEBUNAN NUSANTARA VII (PERSERO) LAMPUNG - Devi Yulianti (SOSIOLOGI: Jurnal Ilmiah Kajian Ilmu Sosial dan Budaya, 2015)
The research about the restructuring in public enterprice is one of the way to develop the corporation, running by a qualitative approach and descriptive type of research in order to give the analysis and descripton about the restructring program in PTPN VII (Persero) Lampung. Thersearch got the data from documentation and litetarute or references about the subject matter. The result of this research showed that there were lots of changes in organization structure during the period of 2009 until 2014. It showed that this corpaoration has done some resctruturing ways suchas: asets, organization, and finance.